Search for exotic decays of the Higgs boson into bb[bar] and missing transverse momentum in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2022)
A search for the exotic decay of the Higgs boson (H) into a bb¯¯ resonance plus missing transverse momentum is described. The search is performed with the ATLAS detector at the Large Hadron Collider using 139 fb−1 of pp collisions at s√ = 13 TeV. The search targets events from ZH production in an NMSSM scenario where H → χ∼02χ∼01, with χ∼02 → aχ∼01, where a is a light pseudoscalar Higgs boson and χ∼01,2 are the two lightest neutralinos. The decay of the a boson into a pair of b-quarks results in a peak in the dijet invariant mass distribution. The final-state signature consists of two leptons, two or more jets, at least one of which is identified as originating from a b-quark, and missing transverse momentum. Observations are consistent with Standard Model expectations and upper limits are set on the product of cross section times branching ratio for a three-dimensional scan of the masses of the χ∼02, χ∼01 and a boson.
*The ATLAS Collaboration: G. Aad, F. Bartels, F.L. Castillo, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und sehr viele weitere Personen]
Im Titel steht der zweite Buchstabe b mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 11.02.2022